Investigation of the Lipid-Lowering Effect of Vitamin C Through GSK-3β/β-Catenin Signaling in Zebrafish - Liu, Dongwu; Yu, Hairui; Pang, Qiuxiang; Zhang, Xiuzhen (Frontiers in Physiology, 2018)
Vitamin C (VC) is an essential nutrient for most fish species because of the absence of L-gulonolactone oxidase in the bodies of fish. VC plays a significant role in maintaining the physiological functions and in improving the growth performance, immunity, and survival of fish. In this study, zebrafish (Danio rerio) were treated with 8.2, 509.6, and 1007.5 mg/kg VC diets for 2 weeks, and the muscle samples were collected for gene expression analysis and biochemical index analysis. The results indicated that 509.6 and 1007.5 mg/kg VC diets inhibited glycogen synthase kinase-3β (GSK-3β) expression and induced the expression of β-catenin in the muscle of zebrafish. The mRNA expression of CCAAT/enhancer-binding protein α (C/EBPα) and fatty acid synthase (FAS), FAS activity, and the content of glycerol and triglyceride (TG) were decreased in the muscle by 509.6 and 1007.5 mg/kg VC diets. In addition, GSK-3β RNA interference was observed in zebrafish fed with 8.2 and 1007.5 mg/kg VC diets. It was found that GSK-3β RNA interference induced the mRNA expression of β-catenin but decreased the mRNA expression of C/EBPα and FAS, FAS activity, as well as the content of glycerol and TG in the muscle of zebrafish. In ZF4 cells, the mRNA expression of GSK-3β, C/EBPα, and FAS was decreased, but β-catenin expression was increased by 0.1 and 0.5 mmol/L VC treatments in vitro. The glycerol and TG content, and FAS activity in ZF4 cells were decreased by 0.1 and 0.5 mmol/L VC treatments. Moreover, the result of western blot indicated that the protein expression level of GSK-3β was significantly decreased and that of β-catenin was significantly increased in ZF4 cells treated with 0.1 and 0.5 mmol/L VC. The results from in vivo and in vitro studies corroborated that VC exerted the lipid-lowering effect through GSK-3β/β-catenin signaling in zebrafish.